2017
DOI: 10.4103/ijnmr.ijnmr_220_15
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence behaviors and some related factors in kidney transplant recipients

Abstract: Background:Kidney transplantation is the renal replacement therapy of choice for most patients with end-stage renal disease (ESRD), however, adherence to the recommended lifestyle is critical for a positive prognosis. The purpose of this study was to assess adherence to immunosuppressive therapy and lifestyle recommendations along with some related factors among kidney transplant patients.Materials and Methods:In this descriptive analytical study, all patients completed a questionnaire regarding medication int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 24 publications
1
43
0
1
Order By: Relevance
“…We found that lower education and higher BMI are both associated with lower adherence to dietary recommendations. This result is consistent with findings from Hedayati et al 7 who showed in their study that patients with lower social support and education levels have lower adherence to lifestyle recommendations. Social determinants of health are well-known risk factors for access to kidney transplant, 33 , 73 and our study suggests that such factors may play a role in post-KT care as well.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that lower education and higher BMI are both associated with lower adherence to dietary recommendations. This result is consistent with findings from Hedayati et al 7 who showed in their study that patients with lower social support and education levels have lower adherence to lifestyle recommendations. Social determinants of health are well-known risk factors for access to kidney transplant, 33 , 73 and our study suggests that such factors may play a role in post-KT care as well.…”
Section: Discussionsupporting
confidence: 93%
“… 4 , 5 Current literature and interventions have focused overwhelmingly on medication adherence with few looking at adherence to healthcare follow-up 4 , 5 or lifestyle. 7 , 8 From a patient perspective, studies have demonstrated that patients tend to be more adherent to medications than to lifestyle recommendations. 6 , 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…immunosuppressants) 1. The WHO defines medication adherence as a match between patient’s behavior and the medical team’s recommendations 2. Medication non-adherence is the major risk factor for rejection episodes 3.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can contribute to medication or lifestyle compliance issues; these include internal factors such as age and gender and external factors such as family support and patient trust in the healthcare system. Other factors such as medication side effects and recommended food types must be considered as well 12…”
Section: Introductionmentioning
confidence: 99%